EFEKTIVITAS PEMBERIAN CHURROS MIX KELORINA TERHADAP PERUBAHAN STATUS GIZI PADA BALITA STUNTING - Vera Virgia; Widiyawati, Rina (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
The problem of stunting is a classic health problem that is complicated to solve considering the many factors that influence the incidence of stunting itself. Churros, as one of the most popular snacks among the public, can be combined with moringa flour which is rich in nutrients and has been proven clinically and in the field to help overcome the problem of stunting in Indonesia. The purpose of this study was to analyze the effectiveness of giving kelorina churros mix on increasing the weight of toddlers with stunting in the Mojokerto Regency area. The research design used was pre-experimental with a static group comparison design approach. The population in this study were all toddlers with stunting in the Mojokerto Regency under the working area of the Sooko Health Center, Gondang Health Center and Jatirejo Health Center. The variable in this study was the stunting toddler's height. Analysis test was carried out using the Wilcoxon test and the Mann-Whitney test. From the results of the Mann-Whitney test, it was obtained a significance value (p value) of 0.013 <0.05 so it can be concluded that there is a significant difference between the two research groups. Keywords: Churros Mix Kelorina, Stunting, Toddler